What determines consumption of nutritious foods by the urban poor in Africa? - Chege, Christine G. Kiria; Namazzi, Stella; Mutua, Mercy M.; Onyango, Kevin; Jäger, Matthias (Emerald Publishing Limited, 2022)
Malnutrition remains a big public health issue especially in developing countries. The purpose of this paper is to analyze factors that influence consumption of nutrient-rich foods among children aged 6–59 months and women of reproductive age (15–49 years) in the urban informal settlements of Nairobi, Kenya, and Kampala, Uganda. This study uses multicomposite soft porridge as an example of a nutritious product.